New late Pleistocene species of Acharax from Arctic methane seeps off Svalbard. (17th January 2020) - Hansen, Jesper; Ezat, Mohamed M.; Åström, Emmelie K. L.; Rasmussen, Tine L.
Abstract : We report, for the first time, the solemyid Acharax svalbardensis sp. nov., from deep-sea methane seep sites on the western Svalbard margin, 79°N. This species is rather small and so far the northernmost representative of its genus. It is identified based on the following combination of diagnostic characters: umbo 27–30% valve length from posterior margin; H/L ratio ∼0.35; broadly rounded to truncated anterior margin; 15 moderately developed, flat double ribs with middle ribs about as strong as posterior ribs. The shells from Acharax svalbardensis sp. nov. were found in sediment cores from two pockmarks at Vestnesa Ridge at ∼1200 m water depth in the Fram Strait off NW Spitsbergen, Svalbard archipelago. Previously, the vesicomyid bivalves Archivesica arctica and Isorropodon nyeggaensis have been documented from the same pockmarks. Here, we describe the new solemyid species and report its stratigraphical occurrence and co-occurrence with the previously described methane seep-associated vesicomyids. All findings of the vesicomyids and the new solemyid species are restricted to the time interval ∼19, 000–15, 600 cal. years BP, correlating with Heinrich Stadial HS1. This period was characterized by cold surface conditions and extensive ice rafting from sea ice and icebergs in the North Atlantic and Arctic region. Inflow of a warm subsurface current of Atlantic water below the melt water layer led to higher bottom water temperatures at the Svalbard margin than at present. This increase in bottom water temperature probably allowed several methane seep-associated bivalve species to settle for a short period of time, namely the vesicomyids A. arctica and I. nyeggaensis and the new species of the solemyid bivalve genus Acharax described here. http://zoobank.org/urn:lsid:zoobank.org:pub:0AAE625F-2BDB-4ACE-8328-25274D30CDF